2020
DOI: 10.1111/bjh.16618
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine is associated with severity of microvasculopathy in sickle cell disease patients

Abstract: Summary The pathophysiology of sickle cell disease (SCD) includes vasculopathy as well as anaemia. Elevated plasma homocysteine is a risk factor for vascular disease and may be associated with increased risk of vascular complications in SCD patients. In the present study, microvascular characteristics were assessed in the bulbar conjunctiva of 18 paediatric and 18 adult SCD patients, using the non‐invasive technique of computer‐assisted intravital microscopy. A vasculopathy severity index (SI) was computed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…When compared with male patients, the female patients exhibited slightly higher tHCY concentrations (although within normal limits), which has also been reported in a previous study in patients with SCD aged 6-11 years (35). A previous meta-analysis indicated that elevated tHCY levels are linearly associated with physiological dysfunctions in a dose-dependent manner, with each 5-µmol/l increase in tHCY causing a 33.6% increase in the risk for major chronic diseases, such as CVD, cognitive decline, and endothelial dysfunction, contributing to all-cause mortality (27). It has been suggested that the administration of appropriate vitamin-B supplements during childhood could decrease the associated complications observed in SCD (27).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When compared with male patients, the female patients exhibited slightly higher tHCY concentrations (although within normal limits), which has also been reported in a previous study in patients with SCD aged 6-11 years (35). A previous meta-analysis indicated that elevated tHCY levels are linearly associated with physiological dysfunctions in a dose-dependent manner, with each 5-µmol/l increase in tHCY causing a 33.6% increase in the risk for major chronic diseases, such as CVD, cognitive decline, and endothelial dysfunction, contributing to all-cause mortality (27). It has been suggested that the administration of appropriate vitamin-B supplements during childhood could decrease the associated complications observed in SCD (27).…”
Section: Discussionsupporting
confidence: 79%
“…In patients with HbSS, CRP has been reported to be strongly and independently associated with increased mortality (26). It has been reported that in patients with SCD, age appears to be an independent predictor of microvasculopathy, and that the administration of appropriate vitamin B supplements during childhood could potentially decrease the associated complications observed (27). In the present study, when levels of tHCY were considered, almost all children with SCD (98.57%) exhibited normal concentrations, with 1.42% (n=1) of patients in the 11-16-years age group exhibiting concentration in the higher range.…”
Section: Discussionmentioning
confidence: 99%
“…30 Homocysteine is clinically relevant in SCD as it has been shown to increase the risk for VOC, microvasculopathy and furthermore the risk for cardiovascular disease and stroke in patients with SCD. [31][32][33] We observed that the vitamin B 12 tended to be lower in males as compared to females and moreover, males had higher homocysteine levels and lower folate levels as compared to females across all age groups (the gender difference in homocysteine levels was significant in the two adolescent subgroups). Furthermore, studies have shown that supplementation with folic acid can reduce elevated levels of homocysteine.…”
Section: Discussionmentioning
confidence: 74%
“…Given this, we were somewhat surprised that the concentrations of total homocysteine were within the reference range for the majority of our study cohort 30 . Homocysteine is clinically relevant in SCD as it has been shown to increase the risk for VOC, microvasculopathy and furthermore the risk for cardiovascular disease and stroke in patients with SCD 31–33 . We observed that the vitamin B 12 tended to be lower in males as compared to females and moreover, males had higher homocysteine levels and lower folate levels as compared to females across all age groups (the gender difference in homocysteine levels was significant in the two adolescent subgroups).…”
Section: Discussionmentioning
confidence: 74%
“…In fact, the presence of chronic kidney disease in patients with SCD is a risk factor for the development of pulmonary hypertension. 4 In this issue of the Brisith Journal of Haematology, Sammaron et al 8 show that homocysteine is directly correlated with the severity of microvasculopathy, as assessed in vivo through computer-assisted intravital microscopy (CAIM) in the bulbar conjunctiva of adults and children with SCD. The study shows that microvascular damage worsens with age.…”
mentioning
confidence: 99%